Assessment of Masseter Muscle Hardness by Ultrasound Elastography and Hardness Meter in Healthy Individuals – An Observational Study - Deepa Jatti Patil; Rajesh Kumar Rathore; Ashutosh Patel (National Journal of Clinical Anatomy)
Background: Examining the masseter muscle is crucial in assessment of temporomandibular disorders, hypertrophy, and sports injuries. The study aims to assess the hardness of masseter muscle in normal adults by muscle hardness meter and ultrasound elastography. Methodology: Seventy healthy participants were included in the study. The thickness and muscle elasticity index (MEI) of masseter was conducted with the LOGIQ P9 machine by ultrasound elastography. A portable muscle hardness meter was utilized to quantify the stiffness of the masseter muscle. The data were subjected to statistical analysis. Paired sample t-test was used to compare the masseter muscle thickness with MEI. Pearson’s correlation was used to compare the masseter thickness, MEI, and muscle hardness meter values of masseter muscle. Results: The patients’ average age was 33.68 ± 12.68 years. The average values of muscle hardness meter are 0.80 ± 0.08 N and 0.79 ± 0.08 N, masseter thickness 1.03 ± 0.20 cm and 1.034 ± 0.26 cm, and MEI are 1.30 ± 0.30 and 1.32 ± 0.31, respectively, on right and left sides. The MEI values augmented with age bilaterally on both sides. Males had greater masseter muscle thickness in comparison to females. The comparison between hardness values of masseter obtained by hardness meter and MEI by ultrasound elastography and the masseter muscle thickness were assessed by Pearson’s correlation. Hardness meter and MEI association were 0.628, (moderately positive) with a P < 0.001. Conclusion: It was discovered that portable muscle hardness meters and ultrasound elastography are reliable indicators for determining the stiffness and thickness of the masseter muscle. This study provides reference values that can be used for further research.